Behavioral relevance of category selectivity revealed by human ECoG data - Seyedamin Hashemi; Seyed Ali Ebadi; Fatemeh Zareayan Jahromy; Stefan Treue; Gabriel Kreiman; Moein Esghaei (PLoS ONE, 2025)
Object recognition is a crucial brain function that involves a complex interplay between various brain regions. However, the behavioral relevance of functional interactions between these regions remains largely unexplored. In this study, we examined the functional interactions between different brain regions during object recognition using intracranial electrocorticography (ECoG) recordings in subjects diagnosed with pharmacologically intractable epilepsy. We computed the phase locking value (PLV) between different brain areas and its category selectivity, and assessed its behavioral relevance by comparing correctly and incorrectly performed trials. Our results revealed that phase locking between brain regions varies across different object categories and that this variability significantly influences the perceptual behavior of subjects. Importantly, we found that the behavioral relevance of these interactions is spatially organized, with the high behaviorally relevant connections being longer for the frontal lobe and shorter for the occipital lobe. These findings underscore the unique roles of different brain areas in object recognition and pave the way for more nuanced explorations of the interplay between brain regions in object recognition and other cognitive functions.